Determinants of Petroleum Profit Tax Compliance among Oil Companies: A Proposed Model - et al., Abba Ya'u (International Journal of Advanced Science and Technology, 2019)
Energy sector contribute immensely to the economic development of more than 98 countries around the globe. One of the popular energy sectors is oil and gas industry. Oil and gas companies paid huge amount of percentage as tax revenue to the host oil and gas producing countries. Despite the enormous contribution of this sector to the economic growth of virtually most of the oil and gas producing countries, standard tax compliance model relevant to the industry are yet to be developed. To address this issue the current study tent to expand the tax compliance models of Allingham and Sandmo (1972) to incorporate additional two predictor variables relevant to oil and gas industry, these variables are; environmental regulations and royalty rates as well as the moderating effect of tax administration efficiency. The model once validated could be a robust model that accounts for the situational and environmental peculiarity of the oil and gas industry for better understanding of oil companies’ tax compliance behaviors. If validated, the model would have a significant policy implication to the host oil and gas countries, relevant tax authorities and academia at large.